AI-pocalypse now: Automating the systematic literature review with SPARK (Systematic processing and automated review Kit) – gathering, organising, filtering, and scaffolding. - Cameron Frederick Atkinson (MethodsX, 2025)
Researchers today face significant challenges reshaping the landscape of academic, government, and industry research due to the exponential growth of global research outputs and the advent of Generative Artificial Intelligence (GenAI). The annual increase in published works has made it difficult for traditional literature review and data analysis methods to keep pace, often rendering reviews outdated by the time of publication. In response, this methods article introduces a suite of new tools designed to automate a number of stages for systematic literature reviews. Designated SPARK (Systematic Processing and Automated Review Kit), the new computational-based approaches presented in this article automate the collection, organisation, and filtering of journal articles, alongside a data extraction scaffolding technique, for use in a systematic literature review on trauma-informed policing. As global research outputs rise, so does the need for automated methods. This paper highlights how these methods can enhance research efficiency and impact. • Hard-coded tools can be utilised to automate research. • Hard-coded tools do not carry the dangers of ‘hallucinations’ that GenAI infused tools may. • Hard-coded automation tools allow researchers to keep up to date with contemporary research outputs while maintaining a high level of control in the research process.